Russian folk verse and the main approaches to its study - Alexander M. Petrov (Слово.ру: балтийский акцент)
This paper addresses general issues in the study of Russian folk verse. A critical examination of the major theories related to this topic highlights their significance in the history of Russian versification. The unique characteristics of folk verse, which exist in an oral-musical form, necessitate the development of specialized methods for its analysis. While traditional studies of versification offer a variety of methods and resources for analysing different forms of literary verse, they often fall short when applied to folklore verse. A flexible approach to the study of folk poetry is essential, given the diversity of folklore forms. In addition to classical folk accentual verse, many genres adhere to the principles of syllabic-accentual versification. Methods for analysing syllabic texts from other Slavic cultures may also be relevant. Each genre must be contextualized within its historical framework; thus, folklore requires a differentiated analytical approach. Furthermore, the degree of convergence with musicology can vary: in verse linguistics, traditional versification methods may often suffice. The approach based on counting beats holds particular promise, as it relates to the concepts of isochronic metrics, which remain underexplored in the field of Russian folk versification.